Adaptive Speed Control for Autonomous Mobile Robot using Fuzzy Logic Controller - Hamzah, Ahmad; Wan Nur Diyana, Wan Mustafa; Mohd Rusllim, Mohamed (2012)

(untitled)
This paper deals with the development of an adaptive speed controller for autonomous mobile robot using a fuzzy logic controller.The analysis of performance between a system applying triangular membership and a system using gaussian membership is compared to distinguish their differences. The results have shown that the gaussian membership method has improved the tracking performance for the mobile robot to reach its target. This also suggest the same behavior even when a different mobile robot movements is assigned. This paper considers three, five and seven memberships for both techniques to determine their effectiveness and effects to the system performance. The investigation has leads to the conclusion that the gaussian membership has competently surpassed the triangular membership performances even when the robot has different movements to achieve its target.